Frommer's NYC free & dirt cheap - Wolff, Ethan. 4 0 16; 5 (Hoboken, NJ : Wiley Publishing, Inc., 2009)
A guide to visiting New York City for the budget-minded traveler that profiles 382 free or low-cost activities, including plays, concerts, happy hours, films, and classes, and includes maps as well as suggested itineraries.
Map on inside cover.;Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; 20; New York (N.Y.);New York (N.Y.) -- Guidebooks.;Guidebooks.; 2